Risk Factors for Scabies Among Inmates: A Case-Control Study in North Sumatra - Aprida Aulia Rizki; Syafran Arrazy (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2025)
Poor environmental sanitation in correctional facilities contributes to the spread of infectious diseases, especially in crowded conditions. Scabies is generally associated with inadequate personal hygiene and overcrowding. This study aims to examine the relationship between inmates' knowledge, attitudes, and personal hygiene practices with the incidence of scabies in Tanjung Balai Class II B Correctional Institution, North Sumatra. This quantitative case-control study was conducted from February to March 2025. This study involved 160 inmates, consisting of 80 individuals with scabies (cases) and 80 individuals without (controls). Data were analyzed using statistical tests for bivariate tests using the chi-square test to assess the relationship between variables and the test used for multivariate tests using multiple linear regression. This study found a significant association between scabies incidence and knowledge (p-value = 0.000, OR = 3.869), attitude (p-value = 0.000, OR = 3.869), and personal hygiene (p-value = 0.000, OR = 23.222), indicating that inmates with lower knowledge, negative attitudes, and poor hygiene practices were more likely to experience scabies. The results of the logistic regression test showed that the most influential variable was personal hygiene (AOR = 17.58; 95% CI = 4.99–61.94; p < 0.001). These findings suggest that improving inmates' knowledge, attitudes, and personal hygiene practices can reduce the incidence of scabies. It is recommended that medical personnel in correctional institutions provide targeted education to inmates regarding scabies prevention, with a focus on improving knowledge, attitudes, and personal hygiene practices.